2018
DOI: 10.3233/jad-180017
|View full text |Cite
|
Sign up to set email alerts
|

A Clinicopathological Investigation of White Matter Hyperintensities and Alzheimer’s Disease Neuropathology

Abstract: Background: White matter hyperintensities (WMH) on magnetic resonance imaging have been postulated to be a core feature of Alzheimer’s disease. Clinicopathological studies are needed to elucidate and confirm this possibility. Objective: This study examined: 1) the association between ante-mortem WMH and autopsy-confirmed Alzheimer’s disease neuropathology (ADNP), 2) the relationship between WMH and dementia in participants with ADNP, and 3) the relationships among cerebrovascular disease, WMH and ADNP. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
81
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 82 publications
3
81
0
Order By: Relevance
“…SVD may even be involved early in the disease process by accelerating amyloid deposition in AD as a result of impaired perivascular drainage of amyloid- (Grimmer et al, 2012). Similarly, a recent study found that higher volume of ante-mortem WMH volume predicted greater odds of having autopsy-confirmed AD neuropathology, suggesting SVD may contribute to the severity and progression of AD (Alosco et al, 2018). They identified brain regions where lower GM DBM values were related to higher WMH load, indicating atrophy and CVD pathology may act synergistically in contributing to NPS in MCI and AD.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…SVD may even be involved early in the disease process by accelerating amyloid deposition in AD as a result of impaired perivascular drainage of amyloid- (Grimmer et al, 2012). Similarly, a recent study found that higher volume of ante-mortem WMH volume predicted greater odds of having autopsy-confirmed AD neuropathology, suggesting SVD may contribute to the severity and progression of AD (Alosco et al, 2018). They identified brain regions where lower GM DBM values were related to higher WMH load, indicating atrophy and CVD pathology may act synergistically in contributing to NPS in MCI and AD.…”
Section: Discussionmentioning
confidence: 81%
“…WMHs that result from small vessel disease (SVD) have been associated with vascular risk factors, like hypertension (Shim et al, 2015). WMH load has been associated with AD pathology (Alosco et al, 2018;Dadar et al, 2018), and a relationship between SVD and WMH lesions in AD has been reported in other studies (Shim et al, 2015). WMHs of presumed vascular origin have also been associated with NPS in various populations, including AD (Berlow et al, 2010;Dadar, Maranzano, et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…One study used biochemical analysis to show that WMLs are associated with demyelination and degenerative axonal loss, but not ischemic damage, in patients with AD [ 26 ]. Another autopsy study has reported that WMLs are associated with cerebrovascular neuropathology (amyloid angiopathy, microinfarcts, infarcts, lacunes), and tau pathology [ 27 ]. Although the etiology and pathophysiology of WMLs are not fully understood, recent studies have added to the increasing evidence that WMLs are important in the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 AD and cerebrovascular disease (CVD) share risk factors, 9 and although a definite pathomechanistic interaction is not identified, pertinent findings strongly support a vascular component in AD. 8,[10][11][12] Neuropathological studies have revealed that WMHs are of heterogeneous origin, including amyloid angiopathy, arteriolosclerosis, activated glia and axonal rarefaction, [13][14][15] and thus associated with both amyloid pathology and ischemia. Frontal WMHs were recently related to age and vascular risk.…”
Section: Introductionmentioning
confidence: 99%